In Vitro Evaluation of Palestinian Propolis as a Natural Product with Antioxidant Properties and Antimicrobial Activity against Multidrug-Resistant Clinical Isolates - Jamila Daraghmeh; Hamada Imtara (Journal of Food Quality)
The present work reveals, for the first time, the antioxidant and antibacterial properties of propolis samples collected from different regions of Palestine. The content on bioactive compounds has been estimated by total phenolic and flavone and flavonol content, while their antioxidant activity has been determined by radical scavenging methods of 1,2-diphenyl-1-picrylhydrazyl radical (DPPH), 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid) radical (ABTS), and ferric reducing power assay (FRAP). The disc diffusion, minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC) methods were carried out to evaluate the antibacterial activity of Palestinian propolis against multidrug-resistant clinical isolates, including Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, and Streptococcus faecalis. The results showed that the total phenolic content ranged from 9.62 mg to 124.94 mg gallic acid equivalent GAE/g of propolis, and the flavone and flavonol content ranged from 1.06 to 75.31 mg quercetin equivalent QE/g of propolis. The samples S6 from Al-Khalil presented the strongest radical scavenging activity toward DPPH, ABTS free radicals, and FRAP assay with IC50 values of 0.02, 0.03, and 0.05 mg/mL, respectively. The results of antibacterial activity indicated that the propolis samples inhibit the growth of Gram-positive strains better than Gram-negative ones. In addition, a strong correlation was observed between the pH, resin, balsam, total phenolic, flavones and flavonol, and total antioxidant capacity (TAC) from one side and the antibacterial activity of propolis samples except on Pseudomonas aeruginosa.